Draws and windfalls: Comparing patient experiences in inpatient telehealth and non-telehealth acute care units - Geoffrey Silvera; Erin Blanchard; Varun Natarajan; Eric Wallace; William Stigler; Bart Kelly; Terri Scarborough; Sue Feldman (The Beryl Institute, 2023)
The global COVID-19 pandemic has challenged health care delivery in many ways. One solution from the pandemic that offers potential upside is the expansion of telehealth as a means to provide high quality, cost-effective, and safe care while also maintaining excellence in patient and family experience. While most examinations of the use of telehealth over the pandemic have focused on the expansion of outpatient telehealth, few have explored the use of telehealth for hospitalized patients. This article will examine the influence of telehealth use on patient experiences among acute care patients. Inpatient telehealth acute care (ITAC) is a novel modality for hospitalized patients that enables providers to engage with a remote medical unit to ask questions regarding the care plan, medications, and discharge instructions. This case study will compare the experiences of two inpatient hospital units within the same institution to determine the degree to which patient experiences are influenced by telehealth capabilities. The results find that the telehealth unit has negligible differences in patient evaluations of provider communication but shows significant differences in patients' experiences of staff responsiveness and the environmental aspects of care captured via the Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) survey (quietness and cleanliness of care). Future scholarship should seek to determine the extent to which these capabilities influence nurses and other care providers. Experience Framework This article is associated with the Innovation & Technology lens of The Beryl Institute Experience Framework (https://www.theberylinstitute.org/ExperienceFramework). <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22Innovation%20%26%20Technology%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens